Application of a metal naphthalocyanine hole transport material in perovskite solar cells

By using metal naphthalene cyanine compounds as hole transport materials, the thermal stability problem caused by low Tg of Spiro-OMeTAD is solved, and the efficiency and stability of perovskite solar cells are achieved.

CN116940136BActive Publication Date: 2025-04-01DALIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310857187.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-04-01
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

Spiro-OMeTAD has poor thermal stability of perovskite solar cells due to low glass transition temperature (Tg).

Method used

Metal naphthalene cyanine compounds are used as hole transport materials, and the thermodynamic and chemical stability of the material is improved by introducing structural transformation such as naphthalene cyanine rings and central ions.

Benefits of technology

The thermal stability of perovskite solar cells was significantly improved, and the perovskite solar cell devices of Spiro-OMeTAD remained above 80% of their initial photoelectric conversion efficiency (PCE) after 1000h.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116940136B_ABST
    Figure CN116940136B_ABST
Patent Text Reader

Abstract

The invention discloses an application of a metal naphthalocyanine hole transport material in a perovskite solar cell, which belongs to the field of perovskite solar photovoltaic. Metal naphthalocyanine compounds are obtained by linear ring expansion of the phthalocyanine ring. This π-conjugated expansion improves the energy level arrangement, thermal stability, conductivity and hole mobility. The synthesized naphthalocyanine copper hole transport material is applied in a perovskite photovoltaic device, and a photoelectric conversion efficiency of 22.8% and good long-term stability are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of perovskite solar photovoltaics, and specifically relates to the synthesis of a metal naphthalocyanine hole transport material and its application in a perovskite solar cell. Background Art

[0002] In recent years, photovoltaic cells have been undergoing new technological changes around "efficiency and cost". Against the backdrop of new battery technology research and development and industrial application, perovskite photovoltaic cells have gradually shown great commercial prospects due to their superior light absorption characteristics, abundant raw materials, low cost, great potential for improving efficiency, and multiple application scenarios.

[0003] Hole transport materials are a key component in achieving high efficiency and stability of perovskite solar cells. They can not only effectively extract and transport holes at the perovskite / hole transport material interface, but also protect the perovskite crystals from external stimuli and prevent metal diffusion from the electrode. To date, the most successful organic hole transport material is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) to prepare high-efficiency perovskite solar cells. However, due to the low glass transition temperature (T g :122℃) causes the amorphous phase to be unstable, resulting in unsatisfactory thermal stability of the device.

[0004] At present, efficient, stable and low-cost hole transport layers are crucial to promote the commercialization of perovskite solar cells. Commonly used inorganic hole transport materials include NiO x , CuI, CuSCN, CuS and Cu x O, etc., which have excellent thermal stability. However, the performance of inorganic hole transport materials is poor and they are easy to form large clusters, which causes the surface roughness of the prepared hole transport layer to be too large, and it is impossible to form a good interface contact with the active organic layer, and the efficiency performance is much lower than that of organic hole transport materials. Compared with inorganic hole transport layers, organic hole transport materials have many advantages, such as adjustable band gap and energy level, easy synthesis and purification, and solution processability. Summary of the invention

[0005] To solve the problem of Spiro-OMeTAD due to T g In order to solve the problem of poor device stability caused by low ionization temperature, the present invention provides a metal naphthalocyanine hole transport material for perovskite solar cells to replace Spiro-OMeTAD, thereby finally realizing a highly efficient and stable perovskite photovoltaic device.

[0006] Naphthalocyanine compounds introduce a naphthalene ring into each isoindole, which has a larger conjugated system. Naphthalocyanine compounds have richer conjugated π electrons, lower molecular ground state energy, more stable molecular structure, and characteristic absorption peaks in the near-infrared region, and can be used as near-infrared absorbing dyes.

[0007] The technical solution adopted by the present invention is:

[0008] An application of a metal naphthalocyanine compound, the metal naphthalocyanine compound is applied to a hole transport layer of a perovskite solar cell, and the general structural formula of the metal naphthalocyanine compound is shown in Formula 1:

[0009]

[0010] Among them, R 11 -R 46 R is independently selected from hydrogen, straight chain alkyl, branched chain alkyl, straight chain alkoxy, branched chain alkoxy, straight chain alkylthio, branched chain alkylthio, aryl, halogen, carboxyl or cyano; and R 11 -R 46 At least one of them is not hydrogen;

[0011] M is selected from elements such as Li(Ⅰ), Na(Ⅰ), K(Ⅰ), Fe(Ⅱ), Co(Ⅱ), Ni(Ⅱ), Cu(Ⅱ) or Zn(Ⅱ).

[0012] Furthermore, the present invention provides a metal naphthalocyanine hole transport material, the structural formula of the material is:

[0013]

[0014] Among them, R 13 , R 14 , R 23 , R 24 , R 33 , R 34 , R 43 , R 44 are independently selected from linear alkyl, branched alkyl, linear alkoxy, branched alkoxy, linear alkylthio, branched alkylthio, aryl, halogen, carboxyl and cyano; and R 13 , R 14 , R 23 , R 24 , R 33 , R 34 , R 43 , R 44 Not at the same time hydrogen;

[0015] M is selected from Li(Ⅰ), Na(Ⅰ), K(Ⅰ), Fe(Ⅱ), Co(Ⅱ), Ni(Ⅱ), Cu(Ⅱ) or Zn(Ⅱ).

[0016] Due to the presence of naphthalocyanine rings, the molecules have good planarity, good molecular stacking and strong π-π interactions between molecules. The material has high hole mobility, which is beneficial to the extraction and transmission of holes, thereby obtaining high-efficiency perovskite solar cells.

[0017] The metal naphthalocyanine hole transport material is selected from:

[0018]

[0019] Wherein, n is 1-18; M is Fe(Ⅱ), Co(Ⅱ), Ni(Ⅱ), Cu(Ⅱ) or Zn(Ⅱ).

[0020] The introduction of tert-butyl groups with large steric hindrance and alkoxy functional groups of different lengths can effectively increase the solubility of the material, so that the material can be prepared by solution spin coating to obtain a hole transport functional layer of a certain thickness, thereby reducing the manufacturing cost of related photovoltaic devices and obtaining high-efficiency perovskite solar cells.

[0021] The preparation method of the metal naphthalocyanine compound comprises the following steps:

[0022]

[0023] (1) Side chain bromination of o-xylene derivatives using N-bromosuccinimide (NBS);

[0024] (2) The brominated o-xylene derivative is reacted with fumaronitrile to form an intermediate 2,3-dicyano-naphthalene derivative;

[0025] (3) Metal naphthalocyanine compounds were synthesized by template high temperature reaction with 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) as catalyst and corresponding metal salts in a nitrogen atmosphere.

[0026] (4) By using different metal salts as the source of the central element in the last step of the reaction, a variety of different metal naphthalocyanine compounds can be obtained. The metal salts can be metal acetate compounds and metal chlorides.

[0027] (5) The synthesis methods of metal naphthalocyanines substituted with alkoxy groups of different lengths are similar. Considering the post-treatment process, attention should be paid to the protection of relevant functional groups. Taking the straight-chain alkoxy-substituted metal naphthalocyanine compounds as an example, when synthesizing 6-alkoxy-2,3-dicyano-naphthalene using 3,4-dimethylphenol as the raw material, the phenolic hydroxyl group should be protected first before the subsequent reaction, and the subsequent deprotection reaction is also easy to occur. The length of the alkoxy chain is controlled by the halogenated alkyl compound.

[0028] The o-xylene derivative is monosubstituted, disubstituted or fully substituted.

[0029] The metal naphthalocyanine compound mentioned above is used as a hole transport material.

[0030] The solar cell device is a formal structure, including a transparent conductive substrate, a TiO2 or SnO2 electron transport layer, a perovskite light absorption layer, a hole transport layer, a molybdenum oxide layer and a metal electrode; the hole transport layer includes the aforementioned metal naphthalocyanine compound. The preparation process includes cleaning of the conductive substrate, preparation of the electron transport layer by pyrolysis spray method or chemical bath deposition method, preparation of the perovskite light absorption layer by one-step anti-solvent method, spin coating of the hole transport layer, vacuum evaporation of molybdenum oxide and gold electrodes.

[0031] The hole transport layer is prepared by dissolving the metal naphthalocyanine compound in chlorobenzene or 1,2-dichlorobenzene, heating and stirring overnight, adding additives when the solution cools to room temperature, and obtaining a hole transport material solution of the metal naphthalocyanine compound, which is spin-coated on the perovskite light absorption layer.

[0032] 2,3-Dicyanonaphthalene and its derivatives are key intermediates for the synthesis of various naphthalocyanines. The structure of 2,3-Dicyanonaphthalene is:

[0033]

[0034] Among them, the unsubstituted positions (1-8) on the naphthalene ring can be substituted by various substituents to form various derivatives. These derivatives are complexed with different metals to finally obtain naphthalocyanine and its various derivatives. Different substituents, different substitution positions, and different central metals make the physical and chemical properties of metal naphthalocyanine compounds very different.

[0035] The beneficial effects of the present invention are as follows: the present invention provides a metal naphthalocyanine hole transport material for perovskite solar cells. The material has a special skeleton and can be screened and structurally regulated by introducing central ions, axial ligands and substituent groups, thereby obtaining a metal naphthalocyanine material with special physical and chemical stability and special photoelectrochemical functions. The obtained metal naphthalocyanine compound has good thermodynamic and chemical stability, high carrier mobility and good semiconductor properties, and is widely used in optoelectronic devices.

[0036] The metal naphthalocyanine hole transport material disclosed in the present invention has a higher photoelectric conversion efficiency. Compared with Spiro-OMeTAD, the DSC curve of the metal naphthalocyanine hole transport material shows a better T g (252℃), which is much higher than Spiro-OMeTAD; this indicates that metal naphthalocyanine-based hole transport materials have a stable amorphous state, which is beneficial to the thermal stability of the corresponding devices.

[0037] The corresponding perovskite photovoltaic device stability is significantly improved: the PCE of the Spiro-OMeTAD perovskite solar cell device drops sharply, and the PCE after 48h and 96h is 60% and 39% of the original PCE respectively. In contrast, the device based on metal naphthalocyanine hole transport materials maintains more than 80% of its initial PCE after 1000h. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is an electron microscope image of the complete device cross-section of the perovskite solar cell prepared based on the tBu-CuNc hole transport layer in Example 2.

[0039] Figure 2 This is the current density-voltage (JV) curve of the perovskite solar cell device prepared based on tBu-CuNc as the hole transport layer.

[0040] Figure 3 UV-visible absorption spectra of tBu-CuNc in tetrahydrofuran solution and in thin film state.

[0041] Figure 4 This is the DSC curve of tBu-CuNc.

[0042] Figure 5 This is the TGA curve of tBu-CuNc.

[0043] Figure 6 Long-term stability of perovskite solar cell devices based on tBu-CuNc and Spiro-OMeTAD as hole transport layers at 85°C and 85% RH (ISOS-D-3). DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with the accompanying drawings and examples, and the implementation and protection of the present invention are not limited thereto. All technologies covered by the present invention are within the scope of protection. It should be noted that the following description process is achievable or understandable by those skilled in the art based on this specification and with reference to the prior art. The reagents and instruments used can be obtained through commercial channels.

[0045] Example 1 Tert-butyl substituted naphthalocyanine copper

[0046] Based on tert-butyl substituted naphthalocyanine copper (tBu-CuNc) (R 13 , R 23 or R 24 , R 33 or R 34 , R 43 or R 44 The structural formula and synthetic route of (when tert-butyl functional group) are as follows:

[0047]

[0048] The specific synthesis steps are as follows:

[0049] Synthesis of 4-tert-butyl-2,3-tetrabromo-o-xylene intermediate: Add 4-tert-butyl-o-xylene (4.06 g, 0.025 mol), NBS (17.8 g, 0.1 mol), benzoyl peroxide (BPO, 0.1 g), and 50 mL of CCl4 to a 200 mL three-necked flask. Heat under reflux for 12 h under the illumination of two 200 W incandescent lamps. Stop the reaction, the reaction solution is light yellow, and vacuum filtration is used to remove insoluble matter. After rotary evaporation to remove CCl4, 15 mL of n-hexane is added to precipitate a white solid, which is vacuum dried to obtain 7.31 g of product with a yield of 61.2%. 1 H NMR (600MHz, Chloroform-d): δ7.61 (s, 1H), 7.41–7.38 (m, 1H), 7.14 (d, J = 45.1Hz, 1H), 1.34 (s, 9H)

[0050] Synthesis of 4-tert-butyl-2,3-dicyanonaphthalene intermediate: 4-tert-butyl-2,3-tetrabromo-o-xylene (3.84 g, 8 mmol), fumaronitrile (0.63 g, 8 mmol), potassium iodide (7.97 g, 48 mmol) and 50 mL N,N-dimethylformamide were added to a 200 mL round-bottom flask and refluxed at 85 ° C. TLC tracing (petroleum ether: ethyl acetate = 5:1, volume ratio), the raw material point basically disappeared after 12 hours, and the reaction was stopped. After cooling, the reaction mixture was placed in 200 mL of cold water and was a reddish-brown suspension. Adding NaHCO3 solid, the suspension changed from reddish-brown to light yellow. Vacuum filtration, the light yellow filter cake was rinsed with hot water, an appropriate amount of petroleum ether was added for ultrasonication, and the product was filtered and dried to obtain 1.53 g, with a yield of 81.6%. 1 H NMR (600MHz, Chloroform-d): δ 8.31 (d, J = 10.1 Hz, 2H), 7.90 (d, J = 18.2 Hz, 3H), 1.44 (s, 9H).

[0051] Synthesis of tBu-CuNc: Cupric acetate hydrate (0.4 g, 2 mmol), 4-tert-butyl-2,3-dicyanonaphthalene (1.88 g, 4 mmol), anhydrous quinoline (10 mL), and DBU (1.2 mL) were placed in a 100 mL single-mouth round-bottom flask and reacted at 180 ° C for 20 h under nitrogen atmosphere. After the reaction solution was cooled, methanol was added, vacuum filtered, washed with hot water, and dried to collect the crude product. The crude product was separated and purified by silica gel chromatography to obtain dark green solid powder tBu-CuNc (0.98 g, yield 49.0%). MALDI-TOF MS C 64 H 56 N8Cu[M + ]Theoretical calculated value: m / z 999.3924, measured value: m / z 999.3926.

[0052] Example 2

[0053] The preparation process of the perovskite solar cell is as follows:

[0054] (1) The FTO (fluorine doped tin dioxide) transparent conductive substrate was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 minutes and then dried. The conductive substrate was surface treated with ozone UV for 20 minutes.

[0055] (2) Using the chemical bath deposition method, the treated FTO was immersed in a water bath deposition solution. The water bath deposition solution was a mixed solution of 50 mL deionized water, 625 μL hydrochloric acid (37.5%), 12.5 μL thioglycolic acid, 625 mg urea and 137.5 mg stannous chloride dihydrate. The water bath deposition solution was heated to 90 ° C for 4 h, and then the FTO substrate with the SnO2 electron transport layer deposited was ultrasonically cleaned with deionized water and isopropanol, and annealed on a hot plate at 170 ° C for 1 h.

[0056] (3) The perovskite precursor solution consisted of 1.53M PbI2, 1.4M FAI, 0.5M MACl and 0.0122MMAPbBr3, dissolved in 1mL of a mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio of 8:1). The perovskite precursor solution was stirred at 60°C overnight; a two-step spin coating process was used to deposit the perovskite film on the electron transport layer at 2000rpm for 10s and 6000rpm for 30s. 20s before the end of the spin coating process, 100μL of chlorobenzene was quickly dropped on the center of the substrate. After the spin coating process was completed, the substrate was moved to a hot plate and annealed at 100°C for 1h to form a bright and smooth perovskite film.

[0057] (4) Dissolving the corresponding hole transport material in an organic solvent and adding necessary additives to prepare a solution of the corresponding metal naphthalocyanine hole transport material, and spin coating the solution on the perovskite light absorbing layer at a rotation speed of 3000 rpm.

[0058] The tBu-CuNc synthesized in Example 1 was dissolved in 1,2-dichlorobenzene (30 mg mL -1 ), heated at 60°C and stirred overnight. After the solution cooled to room temperature, 15 μL of LiTFSI (170 mg mL -1 , the solvent is acetonitrile) and 15 μL of tert-butylpyridine, and then continue stirring at room temperature for 30 minutes. The prepared hole transport material solution is spin-coated on the perovskite layer.

[0059] (5) Finally, a MoO3 layer with a thickness of about 10 nm and a gold electrode with a thickness of 100 nm were deposited on the hole transport layer by vacuum evaporation.

[0060] The corresponding perovskite solar cell is prepared in this way, and its structure is: FTO / SnO2 / perovskite / tBu-CuNc / MoO3 / Au. The complete device structure is as follows Figure 1 Cross-sectional electron micrograph shown.

[0061] Comparative Example 1

[0062] The rest is the same as in Example 2, except that the hole transport layer is replaced with Spiro-OMeTAD. Spiro-OMeTAD is dissolved in chlorobenzene (90 mg mL -1 ), and then 23 μL LiTFSI (520 mg mL -1 , acetonitrile), 10 μL Co(Ⅲ)-TFSI (375 mg mL -1 , acetonitrile) and 39.5 μL of tert-butylpyridine additive to prepare a hole transport material solution of Spiro-OMeTAD. The perovskite solar cell device in Comparative Example 1 does not deposit a MoO3 layer, and a gold electrode is directly deposited on the perovskite layer. The device structure is: FTO / SnO2 / perovskite / Spiro-OMeTAD / Au.

[0063] The perovskite solar cell prepared in Example 2 was tested. The test conditions were to simulate one sun, and the test standard was IEC 60904-3Ed.2AM1.5G. The JV curve and related photoelectric performance parameters are shown in Figure 2 The photoelectric conversion efficiency (PCE) of the perovskite solar cell based on the tBu-CuNc hole transport layer in Example 2 is 22.8%, wherein the open circuit voltage (V oc ) is 1.14V, short-circuit current density (J sc) is 25.6 mA cm -2 , the filling factor (FF) is 0.78.

[0064] Figure 3 The normalized UV-visible spectra of tBu-CuNc in tetrahydrofuran solution and film state. Both compounds show similar absorption in solution and film state, with clear absorption Q bands, which can be explained by π-π* excitation between bonding and antibonding molecular orbitals. The maximum absorption wavelengths of tBu-CuNc in solution are 773nm. In the film state, compared with the corresponding solution spectrum, tBu-CuNc has a blue shift of 68nm in the Q band, which indicates that tBu-CuNc has strong H aggregation (face-to-face stacking), resulting in a large contact area and strong π-π forces. In tBu-CuNc, the linear ring of the π system provides a specific molecular stacking mode, which will provide superior hole mobility and conductivity. This is beneficial to the corresponding photovoltaic device J sc and FF improvement, as Figure 2 shown.

[0065] Figure 4 and Figure 5 The thermal properties of tBu-CuNc were studied by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Figure 4 The DSC curve of tBu-CuNc shows a better T g (252℃), which is much higher than that of Spiro-OMeTAD. This indicates that tBu-CuNc has a stable amorphous state, which is beneficial to the thermal stability of the corresponding device. Figure 5 Among them, tBu-CuNc has excellent thermal stability, and its thermal decomposition temperature (T d ) is 455℃.

[0066] Figure 6 The perovskite solar cell devices prepared based on Example 2 and Comparative Example 1 were subjected to long-term stability tests at 85°C and 85% RH (ISOS-D-3). The PCE of the perovskite solar cell device prepared based on Comparative Example 1 dropped sharply, and the PCE after 48h and 96h was 60% and 39% of the original PCE, respectively. In contrast, the device based on Example 2 remained above 80% of its initial PCE after 1000h. This is mainly because the tBu-CuNc hole transport material has a much higher T g , which makes it easy for tBu-CuNc to maintain its amorphous properties under thermal stress, thus having excellent thermal stability.

[0067] Example 3 Various tert-butyl substituted metal naphthalocyanines

[0068] The preparation method is the same as that of Example 1, except that copper acetate is replaced by nickel acetate, zinc acetate, and cobalt acetate to obtain tert-butyl substituted naphthalocyanine nickel, naphthalocyanine zinc, and naphthalocyanine cobalt, which are marked as tBu-NiNc, tBu-ZnNc, and tBu-CoNc, respectively.

[0069] (1) tBu-NiNc (1.06 g, yield 53%). MALDI-TOF MS C 64 H 56 N8Ni[M + ]Theoretical calculated value: m / z 994.3981, measured value: m / z 999.4038.

[0070] (2) tBu-ZnNc (0.85 g, yield 43%). MALDI-TOF MS C 64 H 56 N8Zn[M + ]Theoretical calculated value: m / z 1000.3919, measured value: m / z 1000.3920.

[0071] (3) tBu-CoNc (0.93 g, yield 47%). MALDI-TOF MS C 64 H 56 N8Co[M + ]Theoretical calculated value: m / z 995.3960, measured value: m / z 995.3958.

[0072] T of tBu-NiNc, tBu-ZnNc and tBu-CoNc g It is also much higher than Spiro-OMeTAD. This indicates that tBu-NiNc, tBu-ZnNc and tBu-CoNc also have stable amorphous states, which is beneficial to the thermal stability of the corresponding devices.

Claims

1. An application of a metal naphthalocyanine compound, characterized in that: Metal naphthalocyanine compounds are used as hole transport materials in the hole transport layer of perovskite solar cells. The general structural formula of metal naphthalocyanine compounds is shown below: ; Wherein, M is selected from Fe(II), Co(II), Ni(II), Cu(II) or Zn(II).

2. A perovskite solar cell device, characterized in that: The metal naphthalocyanine compound described in claim 1 is used as a hole transport material.

3. A perovskite solar cell device according to claim 2, characterized in that: The structure is a formal structure, comprising a transparent conductive substrate, a TiO2 or SnO2 electron transport layer, a perovskite light absorption layer, a hole transport layer, a molybdenum oxide layer and a metal electrode; the hole transport layer comprises the metal naphthalocyanine compound described in claim 1.

4. A perovskite solar cell device according to claim 3, characterized in that: The preparation process includes cleaning the conductive substrate, preparing the electron transport layer by pyrolysis spray method or chemical bath deposition method, preparing the perovskite light-absorbing layer by one-step anti-solvent method, spin coating the hole transport layer, and vacuum evaporating molybdenum oxide and gold electrodes.

5. A perovskite solar cell device according to claim 4, characterized in that: The hole transport layer is prepared by dissolving the metal naphthalocyanine compound described in claim 1 in chlorobenzene or 1,2-dichlorobenzene, heating and stirring overnight, adding additives when the solution cools to room temperature, obtaining a hole transport material solution of the metal naphthalocyanine compound, and spin coating the solution on the perovskite light absorbing layer.

Citation Information

Patent Citations

  • Organic light-emitting component and method for producing an organic light-emitting component

    CN105723539A